2014
DOI: 10.1128/jb.01589-14
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Genes and Pathways Involved in Surviving Extreme Exposure to Ionizing Radiation

Abstract: To further an improved understanding of the mechanisms used by bacterial cells to survive extreme exposure to ionizing radiation (IR), we broadly screened nonessential Escherichia coli genes for those involved in IR resistance by using transposon-directed insertion sequencing (TraDIS). Forty-six genes were identified, most of which become essential upon heavy IR exposure. Most of these were subjected to direct validation. The results reinforced the notion that survival after high doses of ionizing radiation do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 105 publications
3
48
0
Order By: Relevance
“…2A). The yafC gene encodes a putative transcriptional regulator of unknown function (33). A single base mutation was found in the C terminus of the yafC coding region (D275G), designated yafC* (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A). The yafC gene encodes a putative transcriptional regulator of unknown function (33). A single base mutation was found in the C terminus of the yafC coding region (D275G), designated yafC* (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The underrepresentation of mutants within the IR-challenged samples would suggest that the corresponding genes were involved in mitigating the stress of IR treatment, which is established to cause DNA damage (23,24). Despite decades of research on E. coli DNA repair (24), the authors identified approximately 20 genes not previously known to be important for survival following IR exposure that were missed using classical genetic approaches (18). Similarly, a recent report used Tn-seq to identify genes not previously implicated in the well-studied process of sporulation in Bacillus subtilis (16).…”
mentioning
confidence: 99%
“…1B). There have been multiple methods reported to determine which of the mutants have statistically significant deviations from the wild-type population (5,6,9,(16)(17)(18). The most straightforward method is to apply a Mann-Whitney U test, which makes no assumptions about the underlying distribution of the data (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations